The Phenomenon of Language Disorder in Children With Autism - Husni Mubarok; Lusiana Suciati Dewi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Language is a means of communicating between people, but there are those who are unlucky so that they have language disorders, language disorders are phenomena that occur in a person both in receiving and expressing language in communication, not only parents can be affected by language disorders, children can also receive language disorders because the causes of language disorders vary. This study examines language disorders in children with autism using qualitative research methods, as well as descriptive analysis. The aim is to determine the phenomenon of language disorders in children with autism both in terms of receptive and expressive.